2012
DOI: 10.1017/s0016672312000456
|View full text |Cite
|
Sign up to set email alerts
|

Combining two semidwarfing genesd60andsd1for reduced height in ‘Minihikari’, a new rice germplasm in the ‘Koshihikari’ genetic background

Abstract: Dwarfing in rice has dramatically improved and stabilized rice yields worldwide, often controlled by a single dwarf gene, sd1. A novel semidwarf gene d60 complements the gametic lethal gene gal, such that the F(1) between 'Hokuriku 100' (genotype d60d60GalGal, Gal: mutant non-lethal allele) and 'Koshihikari' (D60D60galgal, D60: tall allele) would show 25% sterility due to deterioration of gametes bearing both gal and d60. The F(2) would segregate as one semidwarf (1 d60d60GalGal) : two tall and 25% sterile (2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…However, in consideration of the maintenance and expansion of genetic diversity, this gene should not be solely relied upon for the development of semidwarf varieties. Through this study, we identified a new semidwarfing gene d60, which shows strong lodging-resistance, and genetically independence from sd1 [23]. Further research could elucidate the function of d60 and enable the development of novel semidwarf rice varieties.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, in consideration of the maintenance and expansion of genetic diversity, this gene should not be solely relied upon for the development of semidwarf varieties. Through this study, we identified a new semidwarfing gene d60, which shows strong lodging-resistance, and genetically independence from sd1 [23]. Further research could elucidate the function of d60 and enable the development of novel semidwarf rice varieties.…”
Section: Discussionmentioning
confidence: 90%
“…To date, there is no evidence that the supposed semidwarf gene d60 is inherited as a single recessive gene according to the ratio of 1D60D60:2D60d60:1d60d60. However, double dwarfness due to a combination of d60 and sd1 was obtained via skewed segregation, and therefore d60 is regarded as an independent allele of sd1 [23].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports indicated that genes can be pyramided to affect PH. Tomita (2012) showed that pyramiding two semidwarfing genes, d60 and sd1, resulted in a PH that was shorter than that using either d60 or sd1. Hu et al (2013) reported that a double mutant of tud1/d61 was shorter than either tud1 or d61, although tud1 and d61 were already two rice dwarf mutants.…”
Section: Complex Regulatory Network For Rice Phmentioning
confidence: 99%
“…Then, we conducted whole-genome analysis of the developed large grain isogenic Koshihikari and identified a gene responsible for the large grain. Furthermore, we developed a large grain/semi-dwarf isogenic line by integrating both the identified large grain gene and the semidwarfing gene d60 [16].…”
Section: Introductionmentioning
confidence: 99%